The Impact of a Strong Bank-Firm Relationship on the Borrowing Firm - Dass, Nishant; Massa, Massimo (Review of Financial Studies, 2011)
[Commercial banks acquire inside information about the firms they lend to. We study the impact of this informationally privileged position on the borrowing firm using a broad panel of U.S. firms over the 1993—2004 period. We measure the strength of the bank-firm relationship by bank-firm proximity, size of the loan, and the lender's insider potential. We show that a stronger relationship, by inducing better monitoring, improves the borrower's corporate governance. Simultaneously, it makes the bank a potentially more informed agent in the equity market. This information asymmetry increases adverse selection for the other market participants and lowers the firm's stock liquidity. This trade-off between improved corporate governance and greater information asymmetry affects the firm's value. Our results have normative implications for the role of banks in the development of financial markets.]